Bronchiolite Aiguë du Nourrisson de Moins de 24 mois à Yaoundé (À Propos de 296 Cas) - Bogne, JB; Chiabi, Andreas; Yatchet Tchatat, Daniela; Nguefack, S; Mah, Evelyn; Tchokoteu, Pierre-Fernand; Mbonda, Elie (HEALTH SCIENCES AND DISEASE, 2013)
ABSTRACT AIM To describe the epidemiology, clinical features, and outcome of acute bronchiolitis in infants in Yaounde. METHODS This was a retrospective and descriptive study on 296 medical records of infants with bronchiolitis seen at the Yaounde Gynaeco-Obstetric and Pediatric Hospital from 1rst January 2008 to 31rst December 2011. Enrolled in the study were infants admitted or not in the hospital with acute bronchiolitis (first or second episode) and aged 24 months or less. The variables studied concerned the epidemiology, clinical features, and outcome. RESULTS Acute bronchiolitis was the third lower respiratory tract infection, and represented 9.4% of all lower respiratory tract infections and 1.6% of all consultations. It occurred mainly in male infants between 2 and 4 months of age, during the rainy season,(September to November), and with a peak of incidence in October. There was a statistically significant seasonal difference in prevalence (P<0.001). A significant annual increase in the incidence, and a relapse rate of 19.6% was noted. The main clinical signs were wheezing, cough, fever, bronchial breath sounds, rhonorrhea and respiratory distress. The overall outcome was good in 98.9% of the patients, and we observed a lethality rate of 1.1%. CONCLUSION Acute bronchiolitis is a public health problem that affects young infants, with a peak incidence during the rainy season. Its incidence is on the rise, and the overall outcome is good. RÉSUMÉ OBJECTIFS Décrire les profils épidémiologiques, cliniques et évolutifs de la bronchiolite aiguë du nourrisson à Yaoundé. MÉTHODES L’étude était rétrospective et descriptive couvrant la période du 1er janvier 2008 au 31 décembre 2011 à l’Hôpital Gynéco-Obstétrique et Pédiatrique de Yaoundé et incluant 296 dossiers médicaux de nourrissons avec diagnostic de bronchiolite aiguë. Les critères d’inclusion étaient les nourrissons reçus en consultation et/ou admis en hospitalisation pour bronchiolite aiguë (1er ou 2ème épisode) et un âge inférieur ou égal à 24 mois. Les variables étudiées étaient d’ordre épidémiologique, clinique et évolutif. RÉSULTATS La bronchiolite aiguë était la troisième infection respiratoire basse (9,4%) et représentait 1,6% des consultations pédiatriques. Les nourrissons du sexe masculin entre 2 et 4 mois étaient les plus touchés, surtout lors de la grande saison des pluies allant de septembre à novembre avec un pic en octobre. Une prévalence saisonnière significative par rapport aux autres mois de l’année a été notée (P<0,001). Une augmentation significative de l’incidence par année a été observée avec un taux de récidive de 19,6%. Les principaux signes cliniques étaient les râles sibilants, la toux, la fièvre, les râles bronchiques, la rhinorrhée, les signes de lutte et la dyspnée. Le pronostic global était favorable dans 98,9% et une létalité de 1,1% a été notée. CONCLUSION La bronchiolite aiguë est un problème de santé publique qui touche les jeunes nourrissons avec un pic épidémique lors de la grande saison des pluies. Son incidence est en augmentation et son pronostic globalement favorable.